Health impacts of climate change and mitigation policies in Ireland - Katie Duffy; Kelly C. De Bruin; Loïc Henry; Clement Kweku Kyei; Anne Nolan; Brendan Walsh (The Economic and Social Research Institute (ESRI), 2024)
The aim of this report is to contribute to the understanding of the link between climate change and health by examining the impact of temperature changes on health and healthcare utilisation in Ireland. While there are multiple dimensions of climate change that may affect health (e.g., increasing temperature, increased precipitation, wildfires, etc.), temperature change is considered one of the principal health threats facing Ireland with respect to climate change. First the report undertakes an in-depth review of the literature on the link between temperature change and health, focusing on evidence from other regions with moderate climates that are similar to Ireland. It also provides an overview of the literature that has assessed the health benefits and co-benefits of climate change mitigation action. Second, the report utilises Met Éireann temperature data to develop Irish climate projections based on simulations performed by the Irish Centre for High-End Computing (ICHEC). Next, the research examines the impact of increases in temperature on use of emergency in-patient hospital care in Ireland. Finally, the report also outlines some of the potential health benefits and co-benefits of climate change mitigation actions, in Ireland.
Keywords: 330; Climate change; Health; Hospital; Forecast; Ireland; Klimawandel; Gesundheit; Krankenhaus; Prognose; Irland